Conformity to zoned urban green spaces in physical development plans: A spatiotemporal analysis of Kisii Town, Kenya - Omollo, Wilfred (Town and Regional Planning, 2023)
Although evidence assessing the provision of urban green spaces (UGS) corroborates their decline, they have, however, not evaluated conformity to zoned UGS in physical development plans (PDPs). To fill the gap, this article examines conformity to zoned UGS in PDPs. It also investigates the drivers of the observed non-conformities. Anchored in the theory of regulatory compliance, the study was undertaken in Kisii Town, Kenya, as a case study of the zoned UGS in the Kisii Town Physical Development Plan (KTPDP). The population comprised a list of 367 developers occupying the zoned UGS, out of which a sample of 186 was randomly selected. Spatial and descriptive data were respectively collected using satellite images and questionnaires. The analysis relied on GIS, descriptive and inferential statistics. Results showed that 75 hectares (ha) of zoned UGS declined by 52% between 2005 and 2022, resulting in a low per capita UGS of 1.95 m2 against the recommended 9 m2. These changes were caused by developing without permits, the County Government of Kisii (CGOK) granting permits to non-applicants, as well as approving developments without the mandatory change or extension of use, insufficient monitoring of developments, laxity in enforcing zoning regulations, and uncertainty in the engagement of registered architects during the development control process. Recommendations are made for a revised physical development plan covering the entire town to provide adequate UGS, ensuring that building plans are submitted by authorised professionals and regular surveillance audits to deter unauthorised developments. The article concludes that, in the absence of effective development control, UGS in Kisii Town will further decline, resulting in the residents not enjoying their acknowledged benefits.